2014
DOI: 10.4161/15548627.2014.981788
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy as a new means of improving chemotherapy efficiency in high-LC3B triple-negative breast cancers

Abstract: The triple-negative breast cancer (TN BC) subtype is the most aggressive form of invasive BC. Despite intensive efforts to improve BC treatments, patients with TN BC continue to exhibit poor survival, with half developing resistance to chemotherapy. Here we identify autophagy as a key mechanism in the progression and chemoresistance of a subset of TN tumors. We demonstrate that LC3B, a protein involved in autophagosome formation, is a reliable marker of poor prognosis in TN BC, validating this prognostic value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 75 publications
(40 reference statements)
9
94
2
2
Order By: Relevance
“…For example, in cancer, autophagy can act as a tumor suppressor during the initial stages of tumor progression, but may promote tumor cell survival in later stages (Tu et al, 2011; Mah & Ryan, 2012; Kaminskyy et al, 2012; Huang et al, 2014; Morgan et al, 2014; Galluzzi et al, 2015). Lefort et al (2014) have shown that autophagy-linked genes are upregulated in TNBC cell lines, including the HCC70 cell line that was used in the current study, cultured in a laminin-rich extracellular matrix (Lefort et al, 2014). Moreover, TNBC cell lines, including HCC70, appear to respond to the suppression of the NEET family proteins, mitoNEET (mNT) and Nutrient-deprivation autophagy factor-1 (NAF-1), with impaired ultrastructural mitochondrial morphology and autophagosome accumulation (Sohn et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…For example, in cancer, autophagy can act as a tumor suppressor during the initial stages of tumor progression, but may promote tumor cell survival in later stages (Tu et al, 2011; Mah & Ryan, 2012; Kaminskyy et al, 2012; Huang et al, 2014; Morgan et al, 2014; Galluzzi et al, 2015). Lefort et al (2014) have shown that autophagy-linked genes are upregulated in TNBC cell lines, including the HCC70 cell line that was used in the current study, cultured in a laminin-rich extracellular matrix (Lefort et al, 2014). Moreover, TNBC cell lines, including HCC70, appear to respond to the suppression of the NEET family proteins, mitoNEET (mNT) and Nutrient-deprivation autophagy factor-1 (NAF-1), with impaired ultrastructural mitochondrial morphology and autophagosome accumulation (Sohn et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…At present, autophagy has become a potential anticancer target both in cancer prevention and therapy, despite its controversial functions including OSCC [13,14,15,16,17]. Reactive oxygen species (ROS) can lead to various effects on different signaling pathways and results in genomic instability by inducing DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism by which autophagy induces cell death is not yet clearly established, it appears to be mediated by the activation of caspase 3 (36). Therefore, in line with such knowledge, co-treatment with chloroquine appears to enhance the effect of many anticancer drugs in vitro as well as in some preclinical models (3741), although a clinical study has yet to confirm its benefit as a co-treatment.…”
Section: Mechanisms Of Action Of Vmp1mentioning
confidence: 92%